Activated platelet membrane nanovesicles recruit neutrophils to exert the antitumor efficiency - Shang, Yinghui; Sun, Juntao; Wu, Xin; Wang, Qinghai (Frontiers in Chemistry, 2022)
Platelets play a crucial role in the recruitment of neutrophils, mediated by P-selectin, CCL5, and ICAM-2. In this study, we prepared platelet membrane nanovesicles from activated platelets. Whether activated platelet membrane nanovesicles can recruit neutrophils has not been reported, nor has their role in antitumor immunity. The results of SDS-PAGE showed that the platelet membrane nanovesicles retained almost all the proteins of platelets. Western blotting showed that both the activated platelets and the platelet membrane nanovesicles expressed P-selectin, ICAM-2, and CCL5. In vivo results of a mouse model of breast cancer-transplanted tumor showed that tumor volume reduced significantly, Ki-67-positive tumor cells decreased, and TUNEL-positive tumor cells increased in tumors after treatment with activated platelet membrane nanovesicles (aPNs). After treatment with aPNs, not only the number of neutrophils, CD8+, CD4+ T cells, and B cells increased, but also IL-12, TNF-α, and IFN-γ levels elevated significantly in tumor tissues.